Adsorption modeling of organic compounds (OCs) by carbon nanotubes (CNTs): role of OC and CNT properties on the linear solvation energy relationship - Gamze Ersan (IWA Publishing, 2021)
This study evaluated a comprehensive database for the adsorption of polar and nonpolar organic compounds (OCs) by carbon nanotubes (CNTs) and to use the linear solvation energy relationship (LSER) technique for developing predictive adsorption models of OCs by multi-walled carbon nanotubes (MWCNTs) and single-walled carbon nanotubes (SWCNTs). The results showed that coefficient of determinations (R2) values for all compounds are higher variability in the 200 g/mol molecular weight cutoff (74–99%). When the molecular weight cutoff of all OCs is higher than 200 g/mol, the trend of their R2 values is decreased (less than 70%). Among all adsorbate descriptor coefficients, V and B terms are the most significant descriptors (p-values ≤ 0.05) in LSER equations for adsorption of low molecular weight polar and nonpolar OCs by both CNTs. Besides, KOW normalization of all Kd values did not have significant impact on the regression of the LSER model, indicating that hydrophobic interactions are not sole mechanism for the adsorption of OCs on CNTs. Lastly, SWCNTs exhibited higher polar OCs uptake than MWCNTs, which was attributed to more polar surface of SWCNTs as suggested by its high oxygen content (%10). HIGHLIGHTS Adsorption data for 119 OCs by MWCNTs and 45 OCs by SWCNTs were modeled.; Adsorption of low/high molecular weight polar and nonpolar OCs by both CNTs predicted.; V and B terms are the most significant descriptors (p-values ≤ 0.05) in LSER equations.; KOW normalization of all Kd values did not significant impact on the LSER model.; SWCNTs exhibited higher polar OCs uptake than MWCNTs.;